MICHAEL ONDAATJE’S RUNNING IN THE FAMILY: A CASE OF SELF IDENTITY - Yameen, Ayesha; Yameen, Haniya (PEOPLE: International Journal of Social Sciences, 2019)
Running in the family is more than an autobiography of Ondaatje. Quite contrary to the purpose of narrating his history, Ondaatje uses it as a means to locate and discover himself through his writing. The basic quest of Ondaatje’s novel is to search for his identity in the mirrors of his past. The quest for his history, is in fact a quest for himself and he mounts on this quest through the novel ‘Running in the Family’. “Ondaatje’s relationship to his past is in process-and the text itself is an exploration of that process (Joanne 45-6).” He tries to locate himself in the shadows of his father, his native land Ceylon, his family relationships and tries to piece together the random, frivolous life that he remembers of Ceylon. And it is heartening to realize in the first chapter that Ondaatje has absented himself from his own autobiography in lieu of his perception that his own identity can only be located if he anchors the identity of the peripheral characters.